2021
DOI: 10.1038/s41419-021-04333-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic inhibition of RIPK3 ameliorates functional outcome in controlled cortical impact independent of necroptosis

Abstract: Traumatic brain injury (TBI) is a leading cause of death and disability with no specific effective therapy, in part because disease driving mechanisms remain to be elucidated. Receptor interacting protein kinases (RIPKs) are serine/threonine kinases that assemble multi-molecular complexes that induce apoptosis, necroptosis, inflammasome and nuclear factor kappa B activation. Prior studies using pharmacological inhibitors implicated necroptosis in the pathogenesis of TBI and stroke, but these studies cannot be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…4, 6; Supplementary Fig. 13,21,[23][24]. Additionally, we observed some differences in the inflammatory markers' secretion and the response to P110 treatment between tricultures with iPSC microglia and HMC3 cells, indicating the importance of the genetic contribution to the severity of injury progression and potential drug treatments.…”
Section: D Bioengineered Triculture Human Tissue Model Of Brain Injur...mentioning
confidence: 81%
See 2 more Smart Citations
“…4, 6; Supplementary Fig. 13,21,[23][24]. Additionally, we observed some differences in the inflammatory markers' secretion and the response to P110 treatment between tricultures with iPSC microglia and HMC3 cells, indicating the importance of the genetic contribution to the severity of injury progression and potential drug treatments.…”
Section: D Bioengineered Triculture Human Tissue Model Of Brain Injur...mentioning
confidence: 81%
“…Next, we looked at the activation of the necroptotic pathway, a known mechanism of neuronal death post-controlled cortical impact injury in rodents (21). We have confirmed necroptotic death execution in Nc and NAMc (the groups that showed neuronal network degeneration) through phosphorylation of mixed lineage kinase (pMLKL), known as necroptotic executor (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in addition to its well-established roles in necroptosis, RIPK3 can also serve as a regulator of inflammation and cell death, independent of necroptotic function. Recent studies have shown that RIPK3 promotes the activation of NLRP3 inflammasomes and contributes to inflammation in an MLKL-independent manner ( 29 , 30 ). The combined application of MLKL -deficient mice in future studies is recommended to provide more robust evidence of the involvement of necroptosis in RAP progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, this function was not found to be dependent on the expression level of RIPK3 in the cells, indicating that RIPK3 might not act through classical inflammatory pathways ( 36 ). RIPK3 has also shown inflammation-modulating effects in certain types of immune cells, such as monocytes and macrophages ( 37 ); however neither of these cell types were assayed in sarcomas conducted by Shekhar et al ( 36 ).…”
Section: Discussionmentioning
confidence: 99%